Recruiting to cohort studies in specialist healthcare services: Lessons learned from clinical research nurses in UK cleft services. Issue 5 (11th January 2018) - Zucchelli, Fabio; Rumsey, Nichola; Humphries, Kerry; Bennett, Rhiannon; Davies, Amy; Sandy, Jonathan; Stock, Nicola Marie
Abstract : Aims and objectives: To explore the experiences of clinical research nurses recruiting patients in a large specialist care‐based cohort study. Background: Longitudinal studies are vital to better understand the aetiology and moderators of health conditions. This need is especially salient for congenital conditions, such as cleft lip and/or palate, where establishing large, comprehensive data sets from birth is vital to improve understanding and to inform interventions. Various barriers exist in recruiting patients to large cohort studies. The role of clinical research nurses embedded within health settings has grown over past decades to facilitate data collection, yet challenges remain. Design: Qualitative descriptive study. Methods: Individual semi‐structured interviews with 12 clinical research nurses based in 10 National Health Service cleft services across the UK, recruiting to the Cleft Collective Birth Cohort Study. Results: Of seven emergent themes, three highlighted challenges to recruiting patients, another three described facilitative factors, and one theme overlapped challenges and facilitators. Challenges included the life circumstances of potential participants; language barriers; and limited clinical research nurse time for study. Facilitative factors included integrating research into clinical practice; patient information shared with clinical research nurses; and support from the university‐based research study team. The theme "Method of data collection" related to both challenges and facilitators. Conclusions: The qualitative data from clinical research nurses recruiting to a large birth cohort study provide helpful practical detail for specialist healthcare teams, specialist nurses, clinical research nurses and researchers looking to optimise recruitment and data collection in longitudinal studies. Relevance to clinical practice: The findings suggest the importance of specialist clinical services and research study teams cooperating to embed research into everyday clinical practice, without compromising care. This should facilitate patients' willingness to participate in important research like the Cleft Collective study and provide them with a positive experience of research.